Two Ways Out/Back “Home”: Two Transnational and Literary Perspectives in Chinese Puzzle and Budapeste - Seth A. Compaoré (Vernacular: New Connections in Language, Literature, & Culture, 2018)
In the current global cinematic practices, it almost becomes a natural phenomenon that filmmakers leave home to film in the spaces beyond the borders of their homelands. These films are often categorized as transnational films. According to Hamid Naficy (2003: 204), “transnational films are framed within the “national cinemas” of their host countries and established cinematic genres”. Budapeste (2009) directed by Walter Carvalho and Chinese Puzzle (2013) directed by Cédric Klapisch are both transnational films from two different regions: South America, Mercosul (Brazil) and the European Union (France). Because both films present transitional places (airports) and transnational spaces, the physical spaces and symbolic borders between Brazil and Hungary in Budapeste are clear, as well as the physical cityscapes from France to the Unites States in Chinese Puzzle. However, because these journeys are not just territorial, the displaced main characters find themselves in deeply emotional, literary, and cultural journeys. Therefore, there is a need to rethink the notion of home in these two films. In both films, the notion of an established home is never a one-and-done thing and home is never a definite possession but it follows Gilles Deleuze’s and Félix Guattari’s theory of “becoming.” In this work, I aim to explore, first, the motherland as a place of alienation resulting in the loss of faith in national institutions in Budapeste and Chinese Puzzle. Then, I analyze the juxtaposition of literary migrations in Budapeste and how it contributes to a “non-established home” for Costa, and how finding a new home for him is embracing a Hungarian identity through literary creation. Finally, in Chinese Puzzle, I focus on the perpetual seeking for home by Xavier, the main character, and the city of New York as a utopian space to cure the journeyer from the trauma of his lost homeland.
Keywords: Transnational; home; border-crossing